Biology of the eyelash hair follicle: an enigma in plain sight. (1st April 2016) - Paus, R.; Burgoa, I.; Platt, C.I.; Griffiths, T.; Poblet, E.; Izeta, A.
Summary: Because of their crucial impact on our perception of beauty, eyelashes constitute a prime target for the cosmetic industry. However, when compared with other hair shafts and the mini‐organs that produce them [eyelash hair follicles (ELHFs)], knowledge on the biology underlying growth and pigmentation of eyelashes is still rudimentary. This is due in part to the extremely restricted availability of human ELHFs for experimental study, underappreciation of their important sensory and protective functions and insufficient interest in understanding why they are distinct from scalp hair follicles (HFs) (e.g. ELHFs produce shorter hair shafts, do not possess an arrector pili muscle, have a shorter hair cycle and undergo greying significantly later than scalp HFs). Here we synthesize the limited current knowledge on the biology of ELHFs, in humans and other species, their role in health and disease, the known similarities with and differences from other HF populations, and their intrinsic interethnic variations. We define major open questions in the biology of these intriguing mini‐organs and conclude by proposing future research directions. These include dissecting the molecular and cellular mechanisms that underlie trichomegaly and the development of in vitro models in order to interrogate the distinct molecular controls of ELHF growth, cycling and pigmentation and to probe novel strategies for the therapeutic and cosmetic manipulation of ELHFs beyond prostaglandin receptor stimulation.